Throughfall and Litterfall Fluxes Reveal New Inputs and Foliar Cycling Maintain Pb, Cd, Cu, and Zn Pollution Legacy in Eastern U.S. Temperate Forests - Justin B. Richardson; Minh Tri Truong; Annise M. Dobson (Pollutants)
Atmospheric pollution of metals negatively impacts the health of terrestrial and aquatic plants and animals. Despite implementation of policies that have substantially decreased emissions of metal pollutants, their legacy continues in temperate forest ecosystems across the globe. Here, we evaluated throughfall and litterfall concentrations and fluxes of Cu, Zn, Cd, and Pb via in rural temperate forests along the Appalachian Mountain range in eastern United States. Our five years of data show that throughfall fluxes of Cu, Cd, and Pb have decreased >89% since the 1980s. However, throughfall Zn and litterfall Cu, Zn, and Cd fluxes remain comparable or greater than the 1980s. These results suggest that Cd, Cu, and Pb emissions have decreased, but trees retain and recycle Cd, Cu, and Zn pollution, extending their legacy for decades following the emission.